Co–culture systems of osteoblasts and osteoclasts: Simulating in vitro bone remodeling in regenerative approaches. (May 2020) - Borciani, Giorgia; Montalbano, Giorgia; Baldini, Nicola; Cerqueni, Giorgia; Vitale-Brovarone, Chiara; Ciapetti, Gabriela
Abstract: Bone is an extremely dynamic tissue, undergoing continuous remodeling for its whole lifetime, but its regeneration or augmentation due to bone loss or defects are not always easy to obtain. Bone tissue engineering (BTE) is a promising approach, and its success often relies on a "smart" scaffold, as a support to host and guide bone formation through bone cell precursors. Bone homeostasis is maintained by osteoblasts (OBs) and osteoclasts (OCs) within the basic multicellular unit, in a consecutive cycle of resorption and formation. Therefore, a functional scaffold should allow the best possible OB/OC cooperation for bone remodeling, as happens within the bone extracellular matrix in the body. In the present work OB/OC co-culture models, with and without scaffolds, are reviewed. These experimental systems are intended for different targets, including bone remodeling simulation, drug testing and the assessment of biomaterials and 3D scaffolds for BTE. As a consequence, several parameters, such as cell type, cell ratio, culture medium and inducers, culture times and setpoints, assay methods, etc. vary greatly. This review identifies and systematically reports the in vitro methods explored up to now, which, as they allow cellular communication, more closely resemble bone remodeling and/or the regeneration process in the framework of BTE. Statement of significance: Bone is a dynamic tissue under continuous remodeling, but spontaneous healing may fail in the case of excessive bone loss which often requires valid alternatives to conventional treatments to restore bone integrity, like bone tissue engineering (BTE). Pre-clinical evaluation of scaffolds for BTE requires in vitro testing where co-cultures combining innovative materials with osteoblasts (OBs) and osteoclasts (OCs) closely mimic the in vivo repair process. This review considers the direct and indirect OB/OC co-cultures relevant to BTE, from the early mouse-cell models to the recent bone regenerative systems. The co-culture modeling of bone microenvironment provides reliable information on bone cell cross-talk. Starting from improved knowledge on bone remodeling, bone disease mechanisms may be understood and new BTE solutions are designed. Graphical abstract: Image, graphical abstract